2005
DOI: 10.1093/carcin/bgi034
|View full text |Cite
|
Sign up to set email alerts
|

Periostin induction in tumor cell line explants and inhibition of in vitro cell growth by anti-periostin antibodies

Abstract: Several factors have been shown to promote the growth of colorectal cancers. Here, we provide evidence that periostin, a protein with structural and sequence homology with a TGF-beta-inducible gene, beta ig-h3, is upregulated in colorectal cancers and their liver metastasis, and it may play a role in promoting growth in these tumors. In vitro studies reveal that periostin promotes growth and cell proliferation in colorectal cancers and that this effect can be abrogated with antibodies to periostin. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 14 publications
7
83
0
Order By: Relevance
“…By in situ hybridisation, we identified the tumour cells as the unique source of production of periostin while immunohistochemical analysis demonstrates the presence of periostin only in the juxtatumoral stroma. This is the first report where stromal localization of periostin is described as previous studies have reported localization of periostin in the cytoplasm of other types of cancer cells (Gillan et al, 2002;Bao et al, 2004;Shao et al, 2004;Kim et al, 2005;Tai et al, 2005). Although, we have occasionally detected a cytoplasmic immunoreactivity of periostin in PDAC cells, the stromal localization was always dominant.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…By in situ hybridisation, we identified the tumour cells as the unique source of production of periostin while immunohistochemical analysis demonstrates the presence of periostin only in the juxtatumoral stroma. This is the first report where stromal localization of periostin is described as previous studies have reported localization of periostin in the cytoplasm of other types of cancer cells (Gillan et al, 2002;Bao et al, 2004;Shao et al, 2004;Kim et al, 2005;Tai et al, 2005). Although, we have occasionally detected a cytoplasmic immunoreactivity of periostin in PDAC cells, the stromal localization was always dominant.…”
Section: Discussionsupporting
confidence: 67%
“…A similar structure was reported for fasciclin I, a cell adhesion molecule involved in the development of the central nervous system of insects (Zinn et al, 1988), and for the big-h3 molecule, a secreted protein induced by TGF-b1 which promotes the attachment and spreading of fibroblasts (Skonier et al, 1992;LeBaron et al, 1995). Periostin was found to be overexpressed in various types of human cancer such as lung (Sasaki et al, 2001a), brain (Sasaki et al, 2002), ovary (Gillan et al, 2002), breast (Shao et al, 2004) and colon cancers Tai et al, 2005) and elevated levels have been detected in sera of patients with thymoma (Sasaki et al, 2001b), non-small lung carcinoma (Sasaki et al, 2001c) and breast cancer (Sasaki et al, 2003). Although these reports implicate periostin in tumour spread, the functional role of this protein is poorly described and recent publications report conflicting data.…”
Section: Introductionsupporting
confidence: 53%
“…Periostin is originally identified from osteoblasts and functions as a cell adhesion molecule for preosteoblast and to participate in osteoblast recruitment, attachment and spreading (Takeshita et al, 1993;Horiuchi et al, 1999). Previous studies showed that the expression of Periostin is upregulated in various types of cancer, including head and neck (Gonzalez et al, 2003), colon , Tai et al, 2005, breast , lung (Sasaki et al, 2001c) and ovarian cancer (Gillan et al, 2002). Here, we also found that 68% of OSCC cases expressed Periostin mRNA and 69% of OSCC cases expressed Periostin protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PN is highly expressed in various human cancers, and have suggested that PN promotes tumor growth and metastasis (3)(4)(5). Moreover, PN is believed to promote tumor growth and metastasis, and to be correlated with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%